Soil Reinforcement Model Test Using Timber Pile at Liquefaction Area - . Suyadi; Tri Harianto; A. Bakri Muhiddin; Ardy Arsyad (Civil Engineering Journal, 2023)
Indonesia is a tropical country threatened by many disasters, such as earthquakes and other collateral hazards (liquefaction). Utilization of micro pile on the liquefaction prone areas is quite popular to increase the soil bearing capacity. In this research, Eucalyptus Pellita Timber was used as micro-piles alternatives. This study aims to determine the effect of timber pile addition on soil settlement and the increase in bearing capacity. Some laboratory investigations were conducted, such as timber and soil physical and mechanical characteristics, preloading tests, and seismic load tests by using small-scale shaking table test. The preloading tests were carried out for 40 days, and the settlements were recorded every 24 hours. Subsequently, seismic load tests were conducted on sandy soil with Dr = 40%. The seismic duration was 37 seconds, with PGA = 0.3 g and f = 0.78 Hz. The preloading test results show that Eucalyptus pellita timber piles are able to reduce the settlement by 18%. and from seismic load testing results are able to reduce the settlement by 68% due to earthquake loads with PGA = 0.3g and a frequency of 0.78 Hz on sandy soil with the potential for liquefaction. This is due to the resistance at the tip of the pile and the skin friction on the timber pile. So, from the results of the model test, it shows that the use of Eucalyptus Pelita timber piles can be used as an alternative to handling sandy soils in areas where liquefaction has the potential to occur. Doi: 10.28991/CEJ-2023-09-06-016 Full Text: PDF